Biological Treatment Of Simulated Humic Acid Wasre Water In A Laboratory Scale Aerobic Reactor - yunardi yunardi (Reaktor, 2003)
A laboratory study was  conducted to determine the feasibility of activated sludge reactor for treating humic acid waste waterand examine the effect of the presence of glucose as the second carbon source on treatment performance. Activated sludge obtained from a waste water treatment plant treating domestic wastewater was used as a seed for reactors. Synthetic wastewater containing humid acid as the sole carbon source and glucose as the second carbon source were used as feeds for the reactors operated in a fill-and-draw mode. The result showed  tht the presence of glucose in the wastewater enhanced the production of higher MLSS (mixed liquor suspended solids) than that without of glucose. The TOC (Total Organic Carbon) concentration in both reactors fluctuated greatly until the end of the experiment due to inability of keeping the input TOC at desired level. However the decrease in TOC suggested that there are some microorganisms capable of degrading the humic acid. Addition of glucose to the simulated humic acid wastewater improved the capability of microbes in degrading the acids. Most ammonium nitrogen in the wastewater was converted to nitrate nitrogen. Although the performance was lower compared to that of conventional system, activated sludge process was capable of degrading wastewater containing humic acids.Keywords : activated sludge, ammonium nitrogen, fill and draw, glucose, humic acid, wastewater